Encouraging and Organizing the Private Sector Firms and the Implementation Problems. - Alkizza, Dr.abdelsalam; Alnakat, Dr.Khaled (Dirasat in Economics and Business, 2009)
The Libyan economic policy had been for a long time dependent on the state-owned sector for a number of objectives of which the very important were creating a variety of economic resources and decrease the dependency on the oil industry. According to its failure to achieve the desired objectives, the system has been modified to give role for the private sector to play in developing the country's economy. This research paper ate mpts to explore the effectiveness of the policy implemented to encourage and organising the private sector through a critical investigation of a number of construction companies. The study has used a case study approach and concluded that most of the construction companies can be classified as small and medium enterprises; the growth of this sector is very slow due to ambiguous public strategies; lack of stability in the regulatory system; and the abs ence of the information system according to which the strategies and programs can be assessed.